Analysis of the Coils Used in Soil Drilling (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
In general, following this, the biological system “soil-plant-atmosphere” is considered. An artificial soil-cultivating working body is introduced into this system, which is created according to the biological prototype of a bionic object related to this system and functioning in it. The result is the adaptation of the working organ, bringing it to the resemblance of a living organism and giving it certain geometric shapes, movement dynamics (multi-contact impact) and the properties of a living prototype. In this case, methods of general systems theory, agricultural mechanics, continuum mechanics, integral and differential calculus are used.